Crenças de docentes e discentes: autonomia e motivação na aprendizagem de inglês como língua estrangeira - ANDRADE, Francisco das Chagas Sousa (2024)
This research aims to investigate the relationship between the beliefs of students and teachers regarding the teaching and learning of English as a foreign language, analyzing how these beliefs influence the practices of teaching and learning English in the context of a public school in the municipality of Vargem Grande, MA. To achieve this objective, the following specific objectives were established: identify the beliefs of teachers and students regarding the teaching of English within the school context; analyze the beliefs of teachers and students regarding the teaching of English; assess whether teachers' beliefs influence the motivation and autonomy of students in learning English. The research is guided by the following problem question: “How do beliefs influence the actions of participants?” The methodology adopted is a case study with a qualitative approach, focusing on 3rd-year high school students in the morning and afternoon shifts at the mentioned school. The theoretical framework was built based on relevant authors for each theme addressed. Initially, we directed our attention to the critical reflections of Santana and Kupske (2022) on the evolution of the English language curriculum component in the National Common Curriculum Base (BNCC). For beliefs, authors such as Barcelos (2004, 1995, 2007, 2015, 2013), Kalaja, Barcelos, and Aro (2015), Barcelos and Abrahão (2006), Silva and Rocha (2007), Fiorelli (2017), Shibasaki (2019), and Pimentel (2021) were considered. Motivation was analyzed in light of the theories of Gardner and MacIntyre (2017), Dörnyei, Csizér, and Németh (2006), Renandya (2014), and Dörnyei (2001). Regarding autonomy, the study relied on the contributions of Benson and Voller (1997), Benson (2001), Holec (1981), Little, Dam, and Lienhard (2017), and Leffa (2003), among other authors. The results highlight that the beliefs of students, centered on the importance of English for career advancement, criticism of existing pedagogical practices, and the appreciation of teacher-student interaction, directly influenced their actions. These beliefs shaped expectations, propelled critical reactions, and encouraged the pursuit of autonomy in the educational process. In the realm of teachers, their beliefs about the importance of English and the need to promote autonomy directly influenced their pedagogical practices. Thus, the answer to the problem question reveals that beliefs exert a tangible influence on the actions of participants, shaping the dynamics of teaching and learning English in the analyzed school.